PENGARUH KUALITAS PRODUK, BRAND IMAGE DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG PADA MAHASISWA - AGUNG PRATAMA; REALIZE . (JURNAL ILMIAH SIMANTEK, 2020)
Product quality is a good experience for all customers something that is offered to customers because it satisfies the element of customer satisfaction so competitive in the market. Brand image is a unique set of associations that will be created or managed by marketers. Promotion is the process of corporate communication with interested parties now and in the future as well as the public. Purchasing decisions are consumer decision making that varies, depending on assumptions such as economic views, passive views, cognitive views and emotional views. Samsung Group is one of the world's largest electronics companies. Samsung until now has also become one of the biggest brands in the world by releasing smartphones that have become champions in the smartphone market competition. However, there are still many consumers who are shaken in the decision to purchase this product. This study aims to determine the effect of product quality, brand image and promotion on Samsung smartphone purchasing decisions on students. The population in this study is Samsung smartphone user students. The sample in this study were 385 respondents. The sampling technique used was sampling aksidental. Data analysis method used is descriptive analysis. Hypothesis testing conducted in this study is the t test and f test. The results of the study concluded that product quality, brand image and promotion influence purchasing decisions.